Comparative wood anatomy of two tropical species - Ferreira, Cassiana Alves; Ribeiro, Alessandra de Oliveira; Urbinati, Cláudia Viana; Duarte, Paulo Junio; Mori, Fábio Akira; Moglio, Beatriz Valente (Scientia Agraria Paranaensis, 2020)
Wood Anatomy is science field very relevant to understanding environmental climate changes and important in suggested to species conservation. The present study proposed the characterization of wood anatomy of Inga alba and Tapirira guianensis from two locations in the Legal Amazon, establishing ecological relationships between both and their habitat. The species were described and characterized according to standards for wood anatomy of IAWA. The quantitative data were submitted to ANAVA and later to PCA (principal components analysis). Qualitatively, characters such as slightly different growth layers, bounded by fibrous zones, diffuse porosity, diagonal arrangement, predominantly solitary vessel, simple perforate plate, libriform and septate fibers, heterogeneous rays were common the two species independent sites following the pattern for Tropical rainforests. However, there were quantitative differences for diameter and frequency mm2 of vessel, and frequency of rays per linear mm related in sites where substrates are most nutritious. As for diameter of pits, there were significant differences, however, in this case, related to species. Similarities between qualitative characters suggest that species inserted in the same environment, even if they belong to different rates, can share several adaptive characters.